Factors Influencing Purchase Intention in Mobile Shopping Applications with Satisfaction as Moderating Variable - Yuni Tisna Kumala Sari; Hepy Hefri Aryanto; Pulung Peranginangin (Akademi Akuntansi YKPN Yogyakarta, 2023)
Mobile shopping applications have become popular in the Indonesian e-commerce industry, as mobile shopping provides a distinct shopping experience compared to browser-based shopping. This study seeks to investigate the attitudes of mobile shopping application users as they relate to purchase intention, with satisfaction acting as a moderating variable. Investigating these factors, it gives insights into the aspects that influence user satisfaction and purchase intention which can help business design sales and marketing strategies. This study also aims to fill gaps in the existing literature by categorizing perceived benefits into social value and hedonic value in order to determine their impact on satisfaction when users are using the mobile shopping application. Using online surveys, 307 Indonesian respondents are collected in total. This study's empirical findings indicate that perceived usefulness, perceived enjoyment, perceived risk, social value, and hedonic value are significant predictors of customer satisfaction (STT). Surprisingly, Satisfaction (STT) is found to be insignificantly influenced by Perceived of Use (PEU). Satisfaction (STT) was then found to have a significant effect on users’ purchase intention.